THE EFFECT OF L-LYSINE HCL SUPPLEMENTATION ON THE BODY WEIGHT GAIN, FEED CONSUMPTION AND FEED EFFICIENCY OF BROILERS - Agustina Foni; Charles Venirius Lisnahan; Oktovianus Rafael Nahak (Program Studi Peternakan, Fakultas Pertanian Universitas Timor, 2020)
The purpose of this study was to determine the effect of l-lysine supplementation in feed on the body weight gain, feed consumption, and feed efficiency of broilers. The experiment was conducted at the Laboratory of Animal Husbandry Study Program, Agriculture Faculty, University of Timor, Kefamenanu from December 2019 to January 2020. This study used 80 day-old chicks (DOC) broilers. The method used is a Completely Randomized Design with four treatments and four replications. The treatments give were: T0 (control feed), T1 (control feed + 0.35% l-lysine), T2 (control feed + 0.70% l-lysine), T3 (control feed + 1.00% l -lysine). Data were processed using Variance Analysis, and Duncan test. The results of the statistical analysis showed that the supplementation of l-lysine in the feed had a significant effect on weight gain, feed consumption, and feed efficiency (P<0.05). It was concluded that supplementation of 0.70% l-lysine HCl in feed gave optimum results to weight gain, feed consumption, and feed efficiency of broilers.